PENDIDIKAN AGAMA ISLAM DAN MULTIKULTURALISME (Sumbangsih Agama Islam dalam Membingkai NKRI) - M. Thoyyib (Al Hikmah: Jurnal Studi Keislaman, 2012)
The multicultural values for national unity has been proclaimed by the founding father of Indonesia; At the initial phase of Indonesia's history, this nation has known the foundation of Multiculturalism from thinking his characters. That like the egalitarian principle in writing Abdul Appeared first in 1902 in his Rival duke of Mind, he introduced the term in lieu of noble mind origin. From Soekarno term appears to call for others. Greeting word bung, which means you are an egalitarian form of greeting Because It does not distinguish a hierarchy of social. Likewise in Islam, the history and Teachings of Islam has taught multicultural in three aspects at once, theological perspective first, second and third historical perspective Sociological perspective. Multicultural education paradigm can be applied Islamic owned and corresponds with the principles of national education as set forth in Chapter III, article 4 of Law No. 20 of 2002 on national education system